A case-control study of the joint effect of reproductive factors and radiation treatment for first breast cancer and risk of contralateral breast cancer in the WECARE study. (December 2020) - Brooks, Jennifer D.; Boice, John D.; Shore, Roy E.; Reiner, Anne S.; Smith, Susan A.; Bernstein, Leslie; Knight, Julia A.; Lynch, Charles F.; John, Esther M.; Malone, Kathleen E.; Mellemkjaer, Lene; Langballe, Rikke; et al.
Abstract: Objective: To examined the impact of reproductive factors on the relationship between radiation treatment (RT) for a first breast cancer and risk of contralateral breast cancer (CBC). Methods: The Women's Environmental Cancer and Radiation Epidemiology (WECARE) Study is a multi-center, population-based case-control study where cases are women with asynchronous CBC (N = 1521) and controls are women with unilateral breast cancer (N = 2211). Rate ratios (RR) and 95% confidence intervals (CI) were estimated using conditional logistic regression to assess the independent and joint effects of RT (ever/never and location-specific stray radiation dose to the contralateral breast [0, >0-<1Gy, ≥1Gy]) and reproductive factors (e.g., parity). Results: Nulliparous women treated with RT (≥1Gy dose) were at increased risk of CBC compared with nulliparous women not treated with RT, although this relationship did not reach statistical significance (RR = 1.34, 95% CI 0.87, 2.07). Women treated with RT who had an interval pregnancy (i.e., pregnancy after first diagnosis and before second diagnosis [in cases]/reference date [in controls]) had an increased risk of CBC compared with those who had an interval pregnancy with no RT (RR = 4.60, 95% CI 1.16, 18.28). This was most apparent for women with higher radiation doses to the contralateral breast. Conclusion: Among young female survivors of breast cancer, we found some evidence suggesting that having an interval pregnancy could increase a woman's risk of CBC following RT for a first breast cancer. While sampling variability precludes strong interpretations, these findings suggest a role for pregnancy and hormonal factors in radiation-associated CBC. Highlights: Radiation treatment is associated with increased contralateral breast cancer risk in some women. Reproductive status at the time of treatment may modify this relationship. Some evidence that pregnancy after radiation treatment increases contralateral breast cancer risk.